PSMA-targeted PET imaging for brain metastases from non-prostatic solid tumors: a systematic review - Dall’ Armellina, Sara; Aghakhanyan, Gayane; Rizzo, Alessio; Fanni, Salvatore C.; Aringhieri, Giacomo; Faggioni, Lorenzo; Cioni, Dania; Neri, Emanuele; Volterrani, Duccio; Morbelli, Silvia (Frontiers in Oncology, 2025)
IntroductionProstate-Specific Membrane Antigen (PSMA) is a transmembrane glycoprotein initially identified in prostate cancer (PCa) but also expressed in the neovasculature of various solid tumors. Recently, PSMA PET has emerged as a promising tool for detecting brain metastases (BMs) from non-prostatic cancers, offering diagnostic capabilities in addition to conventional imaging. This systematic review evaluates the role of PSMA-targeted radiopharmaceuticals in imaging BMs, highlighting their comparative diagnostic performance and exploring their potential for theranostic applications.MethodsA systematic review of the literature was conducted following PRISMA guidelines. Studies evaluating the diagnostic accuracy of PSMA PET imaging in identifying brain metastases (BMs) from non-prostatic solid tumors were included. Both full research articles and case reports were considered to capture the breadth of current evidence. The methodological quality of the included studies was assessed using the QUADAS-2 tool, and data were synthesized qualitatively.ResultsThe review includes 23 studies reporting on 77 BMs from diverse primary malignancies, including lung, breast, salivary gland, thyroid, kidney, and melanoma. PSMA PET demonstrated high tumor-to-background ratios (TBR), enabling superior detection of BMs compared to conventional imaging modalities such as contrast-enhanced MRI and [18F]FDG PET. In post-radiotherapy cases, PSMA PET effectively differentiated radionecrosis from tumor recurrence. Moreover, PSMA PET demonstrated superior sensitivity in detecting thyroid metastases compared to traditional scintigraphy methods, highlighting its potential in cases where standard techniques yield inconclusive results.ConclusionsPSMA PET imaging shows significant promise in improving the diagnosis and management of BMs from non-prostatic cancers. While its theranostic applications remain underexplored, initial findings suggest promising avenues for integrating PSMA PET into personalized neuro-oncology care. Future studies should focus on standardizing imaging protocols, exploring PSMA PET utility in diverse tumor subtypes, and validating its role in clinical decision-making to maximize its impact on patient outcomes.